The production cost efficiency of bioindustrial agriculture: A case study in Bengkulu province Indonesia - Kurniati, Novitri; Jafrizal; Putranto, Heri Dwi; Mulyadi, Maheran (Asian Journal of Agriculture and Rural Development, 2026)
Location-specific bioindustrial agriculture integrating coffee and cattle is a farming system that optimally manages and utilizes all biological resources, including biomass or agricultural waste. The issue of productivity in bioindustrial agriculture is closely related to cost efficiency. This study aims to analyze income and the determinants affecting the cost efficiency of coffee–cattle integrated bioindustrial farming. The research was conducted in Rejang Lebong Regency, Bengkulu Province, Indonesia, which is a center of robusta coffee production. A total of 100 farmers were selected using purposive sampling. Data analysis employed the income function and the stochastic frontier cost function using the Maximum Likelihood Estimation (MLE) method. The results showed that the cost efficiency value of integrated coffee–cattle bioindustrial farming is 12.07% and is still at an inefficient level; this is due to the low adoption rate. Factors that significantly influence cost efficiency are revenue, seed price, NPK fertilizer price, calf price, compost price, and labor wages, while feed prices have no significant effect. Meanwhile, factors that significantly affect cost inefficiency include age, number of family members, coffee farming experience, cattle farming experience, and education. The study recommends collaboration between the government, agricultural extension workers, and farmers to develop extension and training programs on location-specific bioindustrial farming. Increased adoption of this system is expected to improve both income and production cost efficiency.